2013
DOI: 10.1902/jop.2012.120467
|View full text |Cite
|
Sign up to set email alerts
|

Boric Acid Irrigation as an Adjunct to Mechanical Periodontal Therapy in Patients With Chronic Periodontitis: A Randomized Clinical Trial

Abstract: The results of this study suggest that boric acid could be an alternative to chlorhexidine, and it might be more favorable because boric acid was superior in whole-mouth BOP as well as PD and CAL reduction for moderate pockets in early time periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 43 publications
3
35
0
1
Order By: Relevance
“…Based on a previous study, in which 0.75% boric acid in the form of solution was used for subgingival irrigation, and where real‐time cell analysis was carried out to examine the cytotoxic effect of a 0.75% concentration of boric acid on human gingival fibroblasts (HGF) and human periodontal ligament fibroblasts (HPDLF), it was found that a 0.75% concentration of boric acid is non‐toxic to HGF and HPDLF . Based on the results of in vitro cytotoxicity experiments performed in a previous study, we decided to use a 0.75% concentration of boric acid (pH 4.9) in this clinical study, but in gel form, for subgingival delivery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a previous study, in which 0.75% boric acid in the form of solution was used for subgingival irrigation, and where real‐time cell analysis was carried out to examine the cytotoxic effect of a 0.75% concentration of boric acid on human gingival fibroblasts (HGF) and human periodontal ligament fibroblasts (HPDLF), it was found that a 0.75% concentration of boric acid is non‐toxic to HGF and HPDLF . Based on the results of in vitro cytotoxicity experiments performed in a previous study, we decided to use a 0.75% concentration of boric acid (pH 4.9) in this clinical study, but in gel form, for subgingival delivery.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that the systemic administration of boric acid in rats affects receptor activator of nuclear factor kappa‐B ligand/osteoprotegerin balance, thus possibly reducing alveolar bone loss by periodontal disease . In a recent study, it was found that subgingival irrigation with boric acid (0.75%) as an adjunct to mechanotherapy in CP patients leads to significant reduction in plaque index (PI), bleeding on probing (BoP), and probing depth (PD), and a gain in clinical attachment level (CAL) …”
Section: Introductionmentioning
confidence: 99%
“…Based on a previous study, in which 0.75% BA in the form of a solution was used for subgingival irrigation, a real‐time cell analyzer was used to examine the cytotoxic effect of a 0.75% concentration of BA on human gingival fibroblasts (HGF) and human periodontal ligament fibroblasts (HPDLF). It was found that a 0.75% concentration of BA is non‐toxic to HGF and HPDLF.…”
Section: Methodsmentioning
confidence: 99%
“…suggested that systemically‐administered BA can reduce alveolar bone loss in the diabetic rat model . AN0128 has demonstrated in vitro activity against several bacteria associated with periodontal disease, namely Prevotella intermedia , Porphyromonas gingivalis , Eubacterium nodatum , and Treponema denticola . In addition, AN0128 has shown inhibition of lipopolysaccharide‐induced tumor necrosis factor‐α release from human monocytes, and thus, this compound exhibits both antibacterial and anti‐inflammatory activity .…”
Section: Introductionmentioning
confidence: 99%
“…Based on conventional periodontal treatment which includes scaling and root planing (S/RP), numerous studies have reported favorable developments in both the clinical and microbial parameters. 5,6 In spite of the successful clinical outcomes, hand instrumentation has several disadvantages, including being time-consuming and exhausting for patients as well as clinicians. 7 Vector ultrasonic system (VUS) (Dürr Dental, BietigheimBissingen, Germany) is used non-surgically for the procedures of subgingival debridement.…”
Section: Introductionmentioning
confidence: 99%